2019
DOI: 10.1016/j.physletb.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Using QCD counting rules to identify the production of gluonium

Abstract: The empirical identification of bound states of gluons has remained a central goal of hadron spectroscopy. We suggest an experimentally challenging, but model-independent way to assess which zero charge, isospin-zero mesons have a large gluonium light-front wavefunction component in the quark and gluon Fock space of QCD. Our method exploits QCD counting rules which relate the power-law fall-off of production amplitudes at high momentum transfer to the meson's twist (dimension minus spin of its minimum interpol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…Recall that for pure non-abelian Yang-Mills there is theoretical evidence that its spectrum is filled by massive states (glueballs) emerging from the self-interactions of the gluons [16][17][18][19]. In full quantum chromodynamics (QCD) these states lead to a new form of matter and studies have identified resonances measured in experiment as having a dominant glueball nature [20][21][22][23].…”
mentioning
confidence: 99%
“…Recall that for pure non-abelian Yang-Mills there is theoretical evidence that its spectrum is filled by massive states (glueballs) emerging from the self-interactions of the gluons [16][17][18][19]. In full quantum chromodynamics (QCD) these states lead to a new form of matter and studies have identified resonances measured in experiment as having a dominant glueball nature [20][21][22][23].…”
mentioning
confidence: 99%
“…(at fixed angle so that t ∝ s). This counting rule has recently been proposed [88,89] to aid with the identification of the scalar glueball among the f 0 states. For the glueballs with J P C = 0 ++ , the minimum Fock space component is | g • g with antialigned gluon spins and no orbital angular momentum.…”
Section: Absence Of Glueballs In Heavy Ion Collisions?mentioning
confidence: 99%
“…Therefore n f + L = 2. This happens to be the slowest falloff among all the Fock space components that can contribute to the quark-gluon Fock expansion of a scalar meson: a few are shown in table 3 adapted from [88].…”
Section: Absence Of Glueballs In Heavy Ion Collisions?mentioning
confidence: 99%
See 2 more Smart Citations